The complete chloroplast genome of Aconitum scaposum. Issue 8 (3rd August 2021) - Zhang, Min; Luo, Jiawei; Su, Lijun; Ding, Qiaojiao; Yin, Xianmei; Hou, Feixia; Gao, Jihai; Peng, Cheng
Abstract: Aconitum scaposum Franch 1894 belongs to the Genus Aconitum and Subgenus Lycoctonum (Ranunculaceae). It is widely distributed in China and adjacent areas, used as herbal medicine and had highy toxic components. This species has little reasearch information, especially its chloroplast (cp) genome information being unclear. Therefore, with the method of high salt and low pH to extract the cp of A. scaposum, we sequenced and assembled the complete cp genome of A. scaposum using Illumina high-throughput sequencing platform. The results showed the cp genome of A. scaposum was 157 688 bp in length, including a pair of inverted repeated regions (IRa 26 156 bp and IRb 26 232 bp, respectively), large single copy region (LSC 69 309 bp) and small single copy region (SSC 16 917 bp). And cp genome of A. scaposum consisted of 145 unique genes, 8 ribosomal RNA (rRNA) genes and 38 transfer RNA (tRNA) genes, with GC content was 38%. Meanwhile, based on the cp complete genome, we performed the phylogenetic tree of 66 species with maximum likelihood (ML) method, respectively. Among them, we selected one Delphinium species as the outgroup and the bootstrap of each braches were greater than 90%. The results indicated that the phylogenetic relationship of A. scaposum was relatively closely related to A. scaposum var. vaginatum compared to other Aconitum species .